Competition, cooperation, and parental effects in larval aggregations formed on carrion by communally breeding beetles Necrodes littoralis (Staphylinidae: Silphinae) - Lis, Natalia; Mądra-Bielewicz, Anna; Wydra, Jędrzej; Matuszewski, Szymon (Wiley, 2024)
Aggregations of juveniles are the dominant forms of social life in some insect groups. Larval societies are shaped by competitive and cooperative interactions of the larvae, in parallel with parental effects. Colonies of necrophagous larvae are excellent systems to study these relationships. Necrodes littoralis (Staphylinidae: Silphinae), a carrion beetle that colonizes cadavers of large vertebrates, forms massive juvenile aggregations. By spreading over carrion anal and oral exudates, the beetles form the feeding matrix, in which the heat is produced and by which adults affect the fitness of the larvae. We predict that exploitative competition shapes the behaviour of N. littoralis larvae in their aggregations. However, cooperative interactions may also operate in these systems due mainly to the benefits of collective exodigestion. Moreover, indirect parental effects (i.e. formation of the feeding matrix) probably modulate larval interactions within the aggregations. By manipulating parental effects (present/absent) and larval density (0.02-1.9 larvae/1 g of meat), we found a strong negative group-size effect on the fitness of N. littoralis, in colonies with parental effects over almost the entire density range, and in colonies without parental effects for densities larger than 0.5 larva/g. This was accompanied by positive group-size effects in terms of development time (it shortened with larval density) and thermogenesis (it increased with larval density). A pronounced positive group-size effect on juvenile fitness was found only in colonies without parental effects and only in the low density range. These results support the hypothesis that larval societies of N. littoralis are shaped by exploitation competition.
This is the accepted version of the following article: Lis, N., Mądra-Bielewicz, A., Wydra, J. and Matuszewski, S. (2024), Competition, cooperation, and parental effects in larval aggregations formed on carrion by communally breeding beetles Necrodes littoralis (Staphylinidae: Silphinae). Insect Science. https://doi.org/10.1111/1744-7917.13353, which has been published in final form at: https://onlinelibrary.wiley.com/doi/10.1111/1744-7917.13353.
Keywords: Intraspecific interactions; Carrion; Larval societies; Group-size effect